Enhancing EFL Learners’ Vocabulary Mastery through Quizlet: A Classroom Action Research Study - Permatasari, Hani Arum; Nurulia, Aulin; Putri, Cantika; Rohayati, Dedeh; Tugiawati, Lilis (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Vocabulary is crucial to language mastery, as it supports developing listening, speaking, reading, and writing skills. However, many students struggle to expand their vocabulary due to limited exposure to authentic language input and ineffective learning strategies. This study is focused on using the digital application Quizlet to enhance students' English vocabulary acquisition through Classroom Action Research (CAR). Quizlet, which incorporates learning strategies such as spaced repetition and retrieval practice, effectively supports vocabulary acquisition and increases learning motivation. Its interactive features, such as live competitions and collaborative learning modes, promote student engagement and autonomy. This study draws attention to the value of Quizlet as a technology-based learning tool that strengthens vocabulary mastery and creates an active, collaborative, and supportive learning environment for English as a Foreign Language (EFL) learners. Contribution to Sustainable Development Goals (SDGs):SDG 4: Quality EducationSDG 9: Industry, Innovation, and InfrastructureSDG 10: Reduced InequalitiesSDG 17: Partnerships for the Goals (potential)